Hydrogenolysis of furfuryl alcohol to 1,2-pentanediol catalyzed by first row transition metal salts - Pratama, Muhammad Rafi; Irnanda, Istifhamy; Situmorang, Hendra Julius; Permana, Yessi; Qurbayni, Siti Hartinah; Wijaya, Husni Wahyu; Arrozi, Ubed Sonai Fahruddin (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
The growing and relatively large market share of 1,2-pentanediol (1,2-PeD) has attracted attention of researchers to find effective and economically viable catalysts. One type of catalyst that can be used for synthesizing this compound is transition-metal-based catalysts, employed in the hydrogenolysis of furfuryl alcohol (FOL). In this study, the hydrogenolysis of furfuryl alcohol were performed with 2-propanol as the hydrogen source and transition metal salts as the catalysts. The used catalysts include first-row early and late transition metals, i.e., ZrOCl2·8H2O, VOSO4·H2O, FeSO4·7H2O, CuSO4·5H2O, NiCl2, Al(NO3)3·H2O, CoCl2, FeCl3·6H2O, and Zn(NO3)2·6H2O. It was found that ZrOCl2·8H2O, VOSO4·H2O, and FeCl3·6H2O demonstrated superior catalytic activity compared to the other catalysts. Optimal reaction conditions for these three catalysts were achieved at 150 °C for 1 hour, using 2-propanol as the hydrogen source. Under these reaction conditions, the ZrOCl?·8H?O catalyst achieved 95.5% conversion of FOL and 30.3% yield of 1,2-PeD, while the VOSO?·H?O catalyst attained 80.5% conversion of FOL and 36.9% yield of 1,2-PeD. Both results were obtained with a low catalyst concentration of 0.6 mmol%. Meanwhile, the FeCl3·6H2O catalyst converted 94.9% of FOL and yielded 30.9% of 1,2-PeD, using a lower catalyst concentration of 0.4 mmol%. Kinetic studies suggested that the reactions likely follow pseudo-first-order kinetics with experimental activation energies (Ea) of 65 kJ/mol, 55 kJ/mol, and 37 kJ/mol for ZrOCl?·8H?O, VOSO?·H?O, and FeCl?·6H?O catalysts, respectively. These findings highlight the potential of transition-metal-based catalysts in achieving high efficiency with low loading, emphasizing their suitability for industrial applications.